Optimization of Alkali Treatment Condition On Tensile Properties of Kenaf Reinforced Polyester Composite Using Response Surface Method - Othman, Mohd Hilmi; Hashim, Mohd Yussni; Mohd Amin, Azriszul; Huat, Ng Chuan; Marwah, Omar Mohd Faizan; Johar, Muhammad Akmal; Ahmad Jamal, Ezazul Fahmee (International Journal of Integrated Engineering, 2018)
The interface bonding from the chemical treatment of the reinforced fibers can be seen as a great factor for mechanical properties on fiber composite. The alkali treatment serves as a method to increases the surface roughness that resulting in better mechanical interlocking and increases the amount of cellulose exposed on the fiber surface. The optimize condition of the alkali treatment on the tensile strength were investigated using response surface method (RSM). The kenaf fiber are treated with different concentration of alkali treatment, soaking time and temperature. The fiber composite was tested using ASTM D638 tensile test to determine the tensile strength. The highest average reading of kenaf reinforced composite is 26.37MPa from the highest percentage of volume fraction which is 25%. The Analysis of variance (ANOVA) was conducted using full quadratic term at the beginning of response surface methodology analysis work. From the response surface plot, the optimum composite tensile strength by setting the immersion temperature ranging at 30Â°C to 80Â°C and alkali concentration of 6% setting. The values of experimental tensile strength can be used on light weight constructional applications, auto-industrial, and many customary products.